MEDIA PEMBELAJARAN PAPAN TULIS AKSARA BALI UNTUK MENINGKATKAN KETERAMPILAN MENULIS AKSARA BALI: Penelitian Tindakan Kelas - I kadek Suwarsana; Ida Bagus Putra Manik Aryana; Ida Ayu Putu Purnami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research aims to improve the Balinese script writing skills of 28 students of class VIII.1 of SMP Negeri 1 Banjarangkan through the use of Balinese script blackboard media. This research is motivated by the low writing ability of students due to limited infrastructure and the dominance of conventional media. Data were collected through observation and tests, then analyzed descriptively qualitatively and quantitatively. The results of the study showed a significant increase in students' writing skills. Initial data showed an average score of 71.82 with a classical completeness of 21.42%. After the application of the media in Cycle I, the average increased to 75.97 (64.28% complete), and reached its peak in Cycle II at 83.14 (96.42% complete). The results of the hypothesis test with a significance of 0.000 (p <0.05) prove that the Balinese script blackboard media has a positive and significant effect in improving students' writing skills. This media is effective in visualizing the structure of the script while creating interactive learning.